2021
DOI: 10.1021/acsabm.1c00311
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Functionalized Ceramic Bone Substitute Promotes Critical-Sized Bone Defect Repair in Rats

Abstract: Ceramic biomaterials are promising alternatives to bone autografts. However, limited bioactivity affects their performance. Therefore, bioactive molecules and cells are often added to enhance their performance. Exosomes have emerged as cell-secreted vesicles, delivering proteins, lipids, and nucleic acids in a paracrine/endocrine fashion. We studied two complementary aspects required for exosome activity/therapy using purified exosomes: first, the intracellular uptake of labeled exosomes and second, the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…We also observed the concentration-dependent effect of CQ on NO production (Figure S3C). MSC exosomes have been reported to have some antioxidant potential due to the presence of active catalases, which are important antioxidant enzymes, and various heat shock proteins (HSP) that can be accounted for its therapeutic effect as observed. ,, The effects of CQ can be attributed to the presence of resveratrol and quercetin as active constituents, which have been reported to alleviate ROS-generated apoptosis in various cells. The bright-field images (Figure S4G) show the migration of HUVEC cells in the presence and absence of exosomes. As we can see in the figure, the cells readily start migrating toward each other in the exosome-treated group, thereby filling the scratch area; however, most of the wound area in the case of the nontreated group was left open.…”
Section: Resultsmentioning
confidence: 96%
“…We also observed the concentration-dependent effect of CQ on NO production (Figure S3C). MSC exosomes have been reported to have some antioxidant potential due to the presence of active catalases, which are important antioxidant enzymes, and various heat shock proteins (HSP) that can be accounted for its therapeutic effect as observed. ,, The effects of CQ can be attributed to the presence of resveratrol and quercetin as active constituents, which have been reported to alleviate ROS-generated apoptosis in various cells. The bright-field images (Figure S4G) show the migration of HUVEC cells in the presence and absence of exosomes. As we can see in the figure, the cells readily start migrating toward each other in the exosome-treated group, thereby filling the scratch area; however, most of the wound area in the case of the nontreated group was left open.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, to achieve good osteoinductivity, some research reported that exosomes were obtained from osteogenic differentiation of MSCs that was induced by chemical compounds in vitro, prior to being utilized for treatment of bone defects in vivo [7,31]. However, osteogenic exosomes induced by chemical compounds rather than the natural osteogenic microenvironment, may have limited clinical translation potential due to safety issues and other possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the augmented cartilage formation found in pellet cocultures of MSCs and chondrocytes primarily relies on the trophic effects of the MSCs, leading to promoting chondrocyte growth and matrix deposition rather than MSCs' trans-differentiation into mature and functional chondrocyte [ 77 ]. Like parental MSCs, MSCs-derived exosomes trigger chondrocyte proliferation by inducing Akt and ERK axis in chondrocytes [ 78 , 79 ]. In addition to the supposed growth factors, miR-135b-enriched exosomes can enhance TGF-β1 expression, increase chondrocyte proliferation, and sustain cartilage repair [ 80 ].…”
Section: The Mechanism Of Action Of Mscs and Derivative Exosomesmentioning
confidence: 99%